The evolution of court within viceregal households in the Americas (1665-1746): the decline of a domestic economy - Jiménez Castillo, Juan (Librosdelacorte.es, 2024)
This article analyses the evolution and development of royal households within the governmental structure of Spanish America between 1665 and 1746. This study aims to provide answers to the governmental crisis that developed in the kingdoms of the Indies after the Crown prohibited viceroys from granting grants and offices to their relatives and servants (1678), which limited the size of viceregal households and their entourages. In short, the purpose is to illustrate how the dismantling of the viceregal domestic structure and the governance from afar affected viceregal households as a nucleus of political power. Este artículo analiza la evolución y desarrollo de las casas reales en el gobierno de la América española entre 1665 y 1746. Este estudio pretende dar respuestas a la crisis gubernativa que se desarrolló en los reinos de Indias tras la prohibición a los virreyes para conceder mercedes y oficios entre sus allegados y criados (1678), la cual redujo la composición de las casas virreinales y sus séquitos. En definitiva, el propósito es dilucidar cómo la descomposición de la estructura doméstica virreinal y el gobierno en la distancia afectó a las casas virreinales como núcleo de poder político.